2004
DOI: 10.1111/j.1365-2133.2004.05866.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical vitamin B12-a new therapeutic approach in atopic dermatitis-evaluation of efficacy and tolerability in a randomized placebo-controlled multicentre clinical trial

Abstract: Topical vitamin B(12) is a new therapeutic approach in atopic dermatitis. These results document a significant superiority of vitamin B(12) cream in comparison with placebo with regard to the reduction of the extent and severity of atopic dermatitis. Furthermore, the treatment was very well tolerated and involved only very low safety risks for the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 21 publications
1
54
0
Order By: Relevance
“…In the trial by Stücker and colleagues, 217 33 cutaneous events were reported, which were all mild except for one, which involved a moderate reaction after applying the placebo cream. Of these cutaneous events, four cases were considered 'probably related' and two cases were 'possibly related' to the application of vitamin B 12 .…”
Section: Harmsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the trial by Stücker and colleagues, 217 33 cutaneous events were reported, which were all mild except for one, which involved a moderate reaction after applying the placebo cream. Of these cutaneous events, four cases were considered 'probably related' and two cases were 'possibly related' to the application of vitamin B 12 .…”
Section: Harmsmentioning
confidence: 99%
“…The two trials 217,218 appear to show a significant beneficial effect of topical vitamin B 12 cream on the severity of eczema. The lack of CIs for the results presented in both trials means that there is no way to judge the statistical robustness of the results.…”
Section: Overall Implications For Research and Practicementioning
confidence: 99%
See 3 more Smart Citations